Immature stages of giants: morphology and growth characteristics of Goliathus Lamarck, 1801 larvae indicate a predatory way of life (Coleoptera, Scarabaeidae, Cetoniinae) - Vendl, Tomáš; Šípek, Petr (ZooKeys, 2016)
The third larval instar of Goliathus goliatus (Drury, 1770), Goliathus orientalis Moser, 1909 and Goliathus albosignatus Boheman, 1857 are described and illustrated for the first time and compared with the immature stages of other Cetoniinae. Larval development of Goliathus goliatus is investigated under laboratory conditions, with particular emphasis on food requirements. These results support the obligatory requirement of proteins in the larval diet. The association between larval morphological traits (e. g., the shape of the mandibles and pretarsus, presence of well-developed stemmata) and larval biology is discussed. Based on observations and the data from captive breeds it is concluded that a possible shift from pure saprophagy to an obligatory predaceous way of larval life occurred within the larvae of this genus, which may explain why these beetles achieve such an enormous size.
Keywords: captive breeding; Afrotropical region; nutrition shift; Goliathus; growth trajectories; rose chafers; larval development; immature stages